Effect of different temperature, initial pH and substrate composition on biohydrogen production from food waste in batch fermentation - Mohd Yasin, Nazlina Haiza; Abdul Rahman, Nor'aini; Ismail, Fadzillah; Mohd Yusoff, Mohd Zulkhairi; Hassan, Mohd Ali (Knowledgia Review, Malaysia, 2009)
The aim of this study was to establish the optimum operating parameters for biohydrogen production from food waste. Batch fermentation was conducted using a 150 mL serum vial incubated in anaerobic condition. Heat-treated Palm Oil Mill Effluent (POME) sludge was used as the seed culture for biohydrogen production. Biohydrogen production was performed at different temperatures (35, 40, 50, 55 and 60°C), initial pH (5, 6, 7 and 8) and various compositions of sludge to substrate (10:90, 20:80, 30:70 and 40:60% (v/v)). The highest biohydrogen yield was 593 mL H2 g-1 carbohydrate for the experiment conducted at a temperature of 55°C, initial pH 7 and composition of sludge to substrate at 30:70% (v/v). The biohydrogen production from the waste was accompanied by the production of organic acids and the ratio of Hac/HBu was 0.87. Treatment efficiency as shown by Total Carbohydrate (TC), Total Suspended Solids (TSS) and Total Volatile Solids (TVS) reduction were 38, 25 and 18%, respectively.